PENGARUH METODE MANAJEMEN STRES DENGAN INTERVENSI TERAPI MUSIK TERHADAP TINGKAT KECEMASAN ANAK PADA TINDAKAN EKSTRAKSI GIGI - Faridha Hanum; Andreasta Meliala; Rina K. Kusumaratna (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Anxiety is a common problem and challenge in dentistry. Some patient experience extreme anxiety leads to avoiding dental assessment and treatment. Anxieties in children patient are generally not knowing and fear of dental assessment and treatment. Dental anxiety is managed with non-pharmacology such as music therapy distraction method. Objective: To measure anxiety level on children before and after tooth extraction, with and without using music therapy intervention. To measure parent satisfaction before and after stress management interventions using music therapy Methods: This quasi-experimental research used pre-test posttest non-equivalent control group design approach throughout April The total of research subject were 48 respondent. The respondents included paediatric patients with age group of 810 years old at Klinik Utama Bona Medika, Kota Cilegon. Subjects are categorized to intervention and control group. The assessment of patient anxiety level using psychological parameter based on Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS) questioner and physiological using pulse. The research result data is tested using paired t-test to identify the mean score different of anxiety between intervention and control group. Results: The result of paired t-test data shows there is significant different in anxiety between intervention and control group with p=0,000 (p<0,05) value. Conclusion: Music therapy as stress management method lowers the anxiety in children during tooth extraction.